Configurational pathways to effective rural older adult sports participation: a necessity and sufficiency analysis using NCA and QCA - Feng, Huan; Li, YanJin; Wang, XiaoYi; Wang, QingChuan; Wang, ZhiHua (Frontiers in Public Health, 2025)
BackgroundRural older adult populations face significant disparities in sports participation compared to urban areas. Traditional linear analytical approaches often fail to capture the complex configurational nature of effective public service delivery in rural contexts, necessitating sophisticated methodological approaches that accommodate multiple pathways to effectiveness.MethodsThis study employed Necessary Condition Analysis (NCA) and Qualitative Comparative Analysis (QCA) to examine village-level conditions promoting effective rural older adult sports participation in China. Data were collected from 156 villages across three regional contexts, using a multi-stage stratified sampling design. Seven conditions were analyzed: Leadership Support (LD), Planning Systems (PS), Specialized Personnel (PN), Funding Allocation (FD), Facility Infrastructure (FT), Organizational Capacity (OG), and Activity Implementation (AT). NCA identified necessary conditions using ceiling envelopment with free disposal hull (CE-FDH) and ceiling regression with free disposal hull (CR-FDH) techniques, while crisp-set QCA revealed sufficient configurational pathways.ResultsNCA revealed no universally necessary conditions, indicating rural communities can achieve success through multiple alternative pathways without specific prerequisites. QCA identified six distinct sufficient configurations with solution consistency of 0.886 and coverage of 0.43, demonstrating equifinality in rural governance. Specialized Personnel emerged as the only condition present across all pathways (100% frequency), while Leadership Support appeared in five of six solutions (83.3% frequency). Configurations ranged from governance-focused approaches that emphasized leadership coordination to resource-intensive models that integrated formal planning and funding. One pathway achieved effectiveness without traditional Leadership Support, suggesting institutional systems can substitute for individual leadership commitment.ConclusionThe absence of necessary conditions challenges policy frameworks assuming uniform implementation requirements and supports flexible, context-responsive governance models. Multiple sufficient pathways indicate that effective rural development strategies should accommodate diverse approaches rather than relying on prescriptive solutions. Specialized Personnel represent a fundamental requirement across all configurations, while frequent “don't care” conditions reveal significant substitutability among governance arrangements. These findings contribute to the application of configurational methodology in public administration, providing practical guidance for adaptive rural development policies tailored to local conditions.